PENGARUH SUPLEMENTASI PROBIOTIK DENGAN DOSIS BERBEDA PADA PAKAN BUATAN TERHADAP KELANGSUNGAN HIDUP DAN PERTUMBUHAN BENIH IKAN JELAWAT (Leptobarbus hoevenii) - Listiyani, Anisa; Isriansyah; Ma’ruf, Mohamad (Program Studi Budidaya Perairan, Fakultas Pertanian, Universitas Sriwijaya, 2023)
The aim of this study was to analyze of the survival rate, growth rate, feed efficiency, and feed conversion ratio and than determine of the best dose for probiotic supplementation on hoven’s carp fish fry (Leptobarbus hoevenii). This study used a completely randomized design (CRD) which consisted of four treatments and three replications. Treatment of artificial feeding with probiotic supplementation as much as 0 ml kg-1 of feed, 4 ml kg-1 of feed, 8 ml kg-1 of feed, and 12 ml kg-1 of feed. The results showed that probiotic supplementation with different doses on artificial feed showed a significant effect on absolut weight growth rate, specific growth rate, feed efficiency, and feed conversion ratio (P<0.05) but did not have a significant effect on survival rate, and total length growth rate on hoven’s carp fish fry (P>0.05). The results of this study also showed that supplementation with probiotic doses of 12 ml kg-1 of feed produced the highest values for total length growth rate, absolut weight growth rate, specific growth rate, survival rate, and feed efficiency, as well as with the lowest feed conversion ratio values.